2012
DOI: 10.1136/archdischild-2012-302724.0455
|View full text |Cite
|
Sign up to set email alerts
|

455 Improvement of Serum Testosterone in Diabetic Rats Treated with Metformin and Nigella Sativa

Abstract: AbstractsResults Both cases presented with abdominal pain and hepatomegaly, combined with nausea and dyspeptic complaints. Laboratory investigation revealed marked elevation of serum transaminase levels. Synthetic function of the liver stayed intact. Abdominal ultrasound showed isolated, homogenous hepatomegaly, without other abdominal abnormalities. In one case liver biopsy was performed, showing hepatic glycogenosis. Other causes for hepatomegaly were excluded. With improved diabetic control all complaints i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…By contrast, we observed that chrysin stimulated mitochondrial autophagy, as it produced an increase in AMPK level and upregulated PGC-1α and LKB1. In addition, PGC-1α is a mitochondrial biogenesis-related gene upregulated by an antioxidant defense system as Nuclear factor-erythroid 2-related factor 2 (Nrf2) that is reduced with age producing brain function decline, which is associated with ROS and mitochondrial dysfunction [60,61]. Nrf2 coordinates detoxification and antioxidant genes as NQO1 and HO-1 expression [62].…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, we observed that chrysin stimulated mitochondrial autophagy, as it produced an increase in AMPK level and upregulated PGC-1α and LKB1. In addition, PGC-1α is a mitochondrial biogenesis-related gene upregulated by an antioxidant defense system as Nuclear factor-erythroid 2-related factor 2 (Nrf2) that is reduced with age producing brain function decline, which is associated with ROS and mitochondrial dysfunction [60,61]. Nrf2 coordinates detoxification and antioxidant genes as NQO1 and HO-1 expression [62].…”
Section: Discussionmentioning
confidence: 99%
“…MF showed close synergistic interaction with other drugs, like rapamycin, in the rat model of testicular torsion/detorsion-induced ischemia/reperfusion [ 93 ]. Additionally, MF and the Nigella sativa dietary supplement synergistically improved serum testosterone in diabetic rats [ 94 ].…”
Section: Discussionmentioning
confidence: 99%